2017
DOI: 10.4103/0259-1162.206276
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-dose ketamine as sole analgesic agent in maintaining analgesia and intraoperative hemodynamics during laparoscopic gynecological surgeries

Abstract: Background:Ketamine, in low doses, is known to possess intense analgesic properties. The available literature shows wide variation regarding the time and dose of administration of ketamine during surgery.Aim:The aim of this study was to evaluate the effect of intraoperative administration of ketamine when used as sole analgesic in low doses, on hemodynamics and postoperative analgesia in patients undergoing laparoscopic gynecological surgery and compared on the basis of duration of surgery.Settings and Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Figure 4 shows comparison of Ramsay Sedation Score (RSS) between Ketamine and Control group at different time intervals over 24 hours. Both the groups had comparable Ramsay sedation score at 90 mins till 24 hours which is also in accordance with the study conducted by Guignard et al, 8 Saxena et al, 14 they used low dose Ketamine as sole analgesic in patients undergoing laparoscopic gynecological surgeries and observed that in only 3 patients (4.28%) a Ramsay sedation score of 5 was seen just after extubation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 4 shows comparison of Ramsay Sedation Score (RSS) between Ketamine and Control group at different time intervals over 24 hours. Both the groups had comparable Ramsay sedation score at 90 mins till 24 hours which is also in accordance with the study conducted by Guignard et al, 8 Saxena et al, 14 they used low dose Ketamine as sole analgesic in patients undergoing laparoscopic gynecological surgeries and observed that in only 3 patients (4.28%) a Ramsay sedation score of 5 was seen just after extubation.…”
Section: Discussionsupporting
confidence: 90%
“…Ketamine, an NMDA receptor antagonist, is an interesting option. The various studies [8][9][10][11][12][13][14][15] as per the site of surgery, duration and dosing regimen of low-dose ketamine warrants its promising profile in management of post-op pain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed its ability to effectively control pain and minimize opioid use intraoperativly. 30 There is also evidence that intraoperative ketamine use results in improved postoperative pain control and decreased need for postoperative opioids. 31,32 Although thoracic blocks were looked at before in autologous breast reconstruction, 24,28 complete thoracic block including a parasternal block has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We noted that the use of intraoperative ketamine in our protocol was associated with less TMEC. Recent studies showed its ability to effectively control pain and minimize opioid use intraoperativly 30 . There is also evidence that intraoperative ketamine use results in improved postoperative pain control and decreased need for postoperative opioids 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…which demonstrated that ketamine in a dose of 0.5 mg.kg -1 preoperatively followed by repeated doses of 0.25 mg.kg -1 every ½ h in patients undergoing laparoscopic gynecological surgery provided stable intraoperative hemodynamics. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%